PEDAGOGICAL INNOVATION IN SOCIAL SCIENCE: DEVELOPING A WATER CYCLE DIORAMA TO SUPPORT EXPERIENTIAL LEARNING IN MADRASAH IBTIDAIYAH - Dwi Pitriani; Fitria Martanti; Ummu Jauharin Farda (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
The learning media for this water cycle diorama is a teaching aid, such as an aquarium, that can help students learn science in class. Material discussing the water cycle is included in this diorama. This media shows how the water cycle occurs on Earth, which students cannot see directly. One of the aims of this research is to evaluate the needs of teachers and students to make water cycle diorama media for class V, MI As Salam. Another objective is to determine the validity of the water cycle diorama learning media for class V MI, As Salam. Development research (R&D) is a type of research. This research uses the Richey and Klein research model, using three stages. Data collection techniques use qualitative and quantitative descriptive analysis techniques. Questionnaires that describe the needs of teachers and students are also used for validation by media experts and material experts. The research results show that the water cycle diorama learning media in science subjects for class V M is very valid to be tested on students. Media experts received a score of 98, an average of 4.9, and a validity percentage of 98%. In contrast, material experts received a score of 72, an average value of 4.8, and a validity percentage of 96%. It can be concluded that the water cycle diorama learning media is declared "very valid."